Polymeric nanoparticles as an alternative for application of gibberellic acid in sustainable agriculture: a feld study - Pereira, Anderson Espirito Santo [UNESP]; Oliveira, Halley Caixeta; Fraceto, Leonardo Fernandes [UNESP] (Nature Research, 2019)
Nanocarrier systems for the encapsulation of agrochemicals can contribute to sustainable agriculture, but few nanosystems have been developed for plant growth regulators (PGRs). The present study evaluated the efects of seed priming using alginate/chitosan (nanoALG/CS) and chitosan/ tripolyphosphate (nanoCS/TPP) containing GA3 on the growth and productivity of Solanum lycopersicum cultivated under feld conditions. The results demonstrated that nanocarrier systems could improve fruit production, with the productivity increasing almost 4-fold using nanoALG/CS-GA3. This pioneering study demonstrates the potential of nanocarrier systems with PGRs for applications in agriculture
Keywords: Polymeric nanoparticles